Reseña de A comparative analysis of the rnajor abstracting and indexing services for library and inforrnation science: with notes on their coverage of archive material - Valencia de Veizaga, Martha (Revista Interamericana de Bibliotecología, 2017)
Reseña de A comparative analysis of the rnajor abstracting and indexing services for library and inforrnation science: with notes on their coverage of archive material